1997
DOI: 10.1088/1355-5111/9/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and transverse-mode selection in quantum-well vertical-cavity surface-emitting lasers: index- and gain-guided devices

Abstract: We study polarization switching and transverse mode competition in Vertical Cavity Surface Emitting Lasers in the absence of temperature e ects. We use a model that incorporates the vector nature of the laser eld, saturable dispersion, di erent carrier populations associated with di erent magnetic sublevels of the conduction and heavy hole valence bands in quantum well media, spin-ip relaxation processes and cavity birefringence and dichroism. We consider both index-guided and gain-guided VCSELs, and we nd tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 61 publications
3
37
0
Order By: Relevance
“…In addition, we studied the polarization properties of the transient response. It had been shown that these devices usually present a dominant polarization state during dc operation [14], [15] and that the characteristic time for achieving this state is of the order of a few nanoseconds [16], [17]. Our measurements complement this knowledge, showing that the two polarization states of all the transverse modes are present during subnanosecond excitation and that they evolve with the same dynamics.…”
Section: Introductionsupporting
confidence: 72%
“…In addition, we studied the polarization properties of the transient response. It had been shown that these devices usually present a dominant polarization state during dc operation [14], [15] and that the characteristic time for achieving this state is of the order of a few nanoseconds [16], [17]. Our measurements complement this knowledge, showing that the two polarization states of all the transverse modes are present during subnanosecond excitation and that they evolve with the same dynamics.…”
Section: Introductionsupporting
confidence: 72%
“…We simulated the model equations with typical parameters indicated in Table I [4], [5], [37]. To study the polarization competition induced by the interplay of current modulation, spatial hole burning and waveguiding effects, we vary the modulation parameters, , , , the carrier diffusion rate, , and the refractive index of the polarization in the active region, .…”
Section: Resultsmentioning
confidence: 99%
“…Full details of the model are given in [5], [37] and thus here we simply highlight its main features. The equations for the two linearly polarized slowly-varying complex amplitudes of the optical field, and , the total carrier density , and the population difference , between the carrier densities with positive and negative spin values, are…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations